Private sector role in community development: a case study on Martin & East (Pty) Ltd approach to "responsible business" - Damon, Linley Cara (Department of Civil Engineering, 2017)
Given persistently high levels of poverty and inequality in South Africa and the government's apparent inability to meaningfully address these, the role of the private sector to provide additional interventions to assist in achieving social support through sustainable community development initiatives is imperative. The case study unpacks Martin & East (Pty) Ltd's (M&E's) approach to Responsible Business (RB). Winfield's (2015) argument for what RB is, lies within the unique contractual relationships that exist between the business enterprise and its stakeholders. It is within the identification of the business' relationships with various stakeholders and in particular, for the purpose of this research, the community as a stakeholder, that we realise the sphere of influence that the business has to possibly affect social change. In order to understand M&E's RB approach in a particular community the case study is further focused on the City of Cape Town project: 216Q/2014/15 Construction of Link Road (City of Cape Town, 2014) to establish the status quo and any opportunities for improvement which may exist. The dissertation draws on semi-structured interviews to understand the interaction of M&E with project stakeholders, identified as the Project Management Team (PMT) and the affected Community. The findings are interpreted through the goals of RB and Community Development (CD) established to evaluate the quality of the relationships created through the project. I argue that there is evidence of achieving these goals. However, the responsibility of CD still lies wholly with local government and the strategies that it puts in place by the setting of Community Participation Goals (CPGs) on its infrastructure projects. It is with regard to their strategy in achieving these CPGs where M&E's RB approach plays a significant role in truly achieving CD in the way that the PMT had intended. M&E's intrinsic values prompted its Project Team (PT) to engage in informal training, treat labour well and abide by contractual obligations as stipulated in the Contract Document governing their roles and responsibilities. Recommendations for M&E business practice include ensuring that the well thought through strategy for their internal community, through the implementation of the Isidima Trust and involvement in education programmes, is translated to the temporary community in which it often finds itself.